ORIENTASI NILAI DALAM PEMBELAJARAN SEJARAH DENGAN MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KEPEKAAN SOSIAL - Stepanus Wasito; Pargito Pargito; Iskandar Syah (Jurnal Studi Sosial / Journal of Social Studies, 2013)
The correlation of value orientations in the teaching of history to increase critical thinking skills and social sensitivity of students.This is a quantitative research, data collection technique used was a questionnaire scale 4 (four), to obtain data on critical thinking skills and social sensitivity, as well as in the form of essay questions to get the orientation of the value of teaching history. The results conclude that : (1) students’ critical thinking skills provide a positive and significant effect on the value orientation of teaching history at 0.957, (2) social sensitivity gives students a postive and significant effect on the value orientation of teaching history at 0,972, (3) The influence of students critical thinking skills of students’ social sensitivity are positive and significant at 0.965, (4) There is a positive and significant correlation between the orientation of history teaching values with increasing critical thinking skills and social sensitivity of 1,699.Keywords: critical thinking skills, social sensitivity, orientation value in learning history